(untitled) (Ustozlar uchun, 2026)
For decades, chronic viral management was defined by the "daily pill." While effective, this regimen imposed significant psychological burdens and risks of non-adherence. The emergence of Long-Acting (LA) antivirals has fundamentally shifted this paradigm. This review examines the pharmacokinetic (PK) and pharmacodynamic (PD) innovations that enable monthly or quarterly dosing for HIV and Hepatitis B. We analyze the role of pro-drug engineering, nanocrystal technology, and the physiological differences between intramuscular (IM) and subcutaneous (SC) delivery. Finally, we address the "Pharmacokinetic Tail" and its implications for viral escape mutations, offering a 2026 perspective on the future of "set-and-forget" medicine.